Duodenal tumors on cross-sectional imaging with emphasis on multidetector computed tomography: a pictorial review - Domenech-Ximenos, Blanca (Diagn Interv Radiol, 2020)
Duodenal tumors are uncommon, but they can cause significant morbidity and mortality. As stomach and colon are more common sites of gastrointestinal malignancies, radiologists sometimes may neglect the duodenum. Multidetector computed tomography (MDCT) and magnetic resonance imaging (MRI) can accurately locate and characterize mass-forming duodenal lesions, making them invaluable for the differential diagnosis and determining management strategies such as biopsy or surgery. Although conventional endoscopy continues to play an important role in the diagnosis of duodenal tumors, MDCT and MRI are very useful for evaluating the duodenal wall, extraduodenal space, and surrounding viscera, as well as the intraluminal content seen on endoscopy. This pictorial review aims to illustrate the most common benign and malignant mass-forming duodenal lesions and to focus on the imaging features that are most helpful in reaching the correct diagnosis.